International Volunteer Tourism: Integrating Travellers and Communities - Wearing, Stephen Leslie (CABI, 2014)
This book revisits and further develops the topics and themes covered in Volunteer Tourism: Experiences That Make a Difference, written over 10 years ago. In Volunteer Tourism, Wearing attempted to develop greater conceptual clariﬁ cation around the notion of ‘alternative tourism’ with a speciﬁ c focus on tourists who volunteer as a part, or for the whole of their travels. The book focused primarily on research carried out in the Santa Elena Rainforest, Costa Rica (Wearing, 1993; Wearing & Larson, 1996; Wearing, 1998, 2009) between the years 1991 and 1994. At this time, the paradigm of volunteer tour- ism was as an extension of ideas on community-based ecotourism ( Wearing & McLean, 1997). Since that time, the majority of Wearing’s ﬁ eldwork has focused on areas closer to home in Australia, particularly Papua New Guinea and other South Paciﬁ c nations. Some of the following stems from the author’s experiences, research and recent publications carried out in these destinations from 2001 to 2012. This book incorporates some of the work written in previous publica- tions with current thinking and research in volunteer tourism. Although international volunteering has existed for a number of years, the industry report ‘Volunteer Travel Insights 2009’ (Nestora et al., 2009) notes that ‘it was not until after the September 11th incident and the Indonesian Tsunami that travellers started to think about this type of travel and the market came to realise that they could volunteer on their vacation’. ‘The rise of volun- teer vacations seems to be the product of a serendipitous alignment: 10 to 15 years ago, at the same time that trips abroad became easier and less expensive and better-traveled Americans began to seek out more unusual travel experiences, volunteering also became the stuff of national conversation’ (McGray, 2004: 1).